An ergometric analysis of age group swimmers. Issue 1 (March 1981) - Armstrong, N.; Davies, B.
Abstract : Thirteen male competitive swimmers (mean age 14.7 years) were studied during maximal exercise on a treadmill, cycle ergometer and biokinetic swim bench. The mean maximal oxygen uptake values elicited (treadmill = 66.5 ml.kg-1 min.-1; cycle ergometer = 61.0 ml.kg.-1 min.-1; biokinetic swimbench = 44.5 ml.kg.-1 min.-1) were higher than those reported elsewhere for children not engaged in intensive training and even when compared with other groups of similarly aged swimmers the values exhibited were some of the highest recorded. The results were directionally similar to those of other studies comparing treadmill and cycle ergometer exercise with the mean maximal oxygen uptake on the cycle ergometer 9% lower than that on the treadmill. There is no other study with which to compare swim bench values but the majority of maximal values were consistently and significantly lower than those achieved on the other ergometers. The swimmers rank within the group was minimally affected by the type of ergometer on which the measurement was made.